Beyond the diffusion of neoliberalism: Embedded reasoning and policy innovation in the origins of the Argentinian currency board - Heredia, Mariana Laura (2021)
Suffering from high rates of inflation since the 1940s and having experienced two hyperinflations at the end of the 1980s, in 2019 Argentina faced an increase of prices of more than 50%. But in the 1990s Argentina achieved price stability and growth at once. What were the sources of such an immediate change? What lessons can be drawn from this experience? As in the 1990s Argentina adopted profound market reforms, stability could be considered an achievement of neoliberal diffusion. Not only international forces were propelling change; the International Monetary Found (IMF) celebrated the success and invited other emerging nations to imitate it. Nevertheless, this perspective underestimates the importance of the local context in the history of neoliberal reforms and overestimates the coherence of external forces. Through the analysis of testimonies of Argentine and foreign officials and the study of declassified documents from the IMF, this paper argues that stability was only achieved after the adoption of a currency board, which was against the recommendation of most foreign officials. Instead of a simple top-down transposition of ideas, the Argentinian case reveals the importance of the agency of technocrats. Their local innovation not only made the diffusion of neoliberalism possible, but it also turned the currency board into one of the global anti-inflationist recipes recommended to other countries, despite its heavy consequences.